RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS ESTIMATION OF DICLOFENAC AND TOLPERISONE IN TABLET DOSAGE FORM - vemula, venkata raveendra babu; Sharma, Pankaj Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: To develop a simple and cost effective reverse phase high performance liquid chromatography method for simultaneous estimation of Diclofenac and Tolperisone in tablet dosage form. Methods: Chromatography was carried out isocratically at 30°C ± 0.5°C on an XDB C-18 column (4.6 x 150mm, 5μ particle size) with a mobile phase composed of acetonitrile -phosphate buffer pH-3 (30:70% v/v) at a flow rate of 1.0 mL/min. Detection was carried out using a PDA detector at 260 nm. Validation parameters were studied as per ICH guidelines. Results: The retention times for Diclofenac and Tolperisone are 2.2 min and 4.7 min respectively. The linearity range for Diclofenac and Tolperisone are 12.5-125µg/mL and 37.5-375 µg/mL respectively. The percentage recoveries of Diclofenac and Tolperisone are 99.96% and 100.65% respectively. The correlation coefficients for both components are close to 1. Conclusion: This method is fast, accurate, precise and sensitive hence it can be employed for routine quality control of tablets containing both drugs in industries. Keywords: RP-HPLC, Diclofenac, Tolperisone, Simultaneous estimation.